2021
DOI: 10.3390/en14133953
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Conjugate Heat Transfer Simulation of Pulsating Flow in Straight and 90° Curved Square Pipes

Abstract: The turbulent pulsating flow and heat transfer in straight and 90° curved square pipes are investigated in this study. Both experimental temperature field measurements at the cross-sections of the pipes and conjugate heat transfer (CHT) simulation were performed. The steady turbulent flow was investigated and compared to the pulsating flow under the same time-averaged Reynolds number. The time-averaged Reynolds number of the pulsating flow, as well as the steady flow, was approximately 60,000. The Womersley nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The inspection of this study explained that eight-vortex chaotic flow enhanced the HC more than the two-vortex steady-state solution. Experimental observation of conjugate HT of turbulent flow is performed by Guo et al [36] in a 90 o curved square tube, where it was suggested the HT in a 90 o bent channel is 20% higher rather than in a straight channel. In the present work, Dolon et al [33] completed spectral-based computational modeling on flow and heat transition for a CRD of strong curvature (0.5) and large aspect ratio (Ar = 4.0) where various flow regimes are obtained and CHT is substantially enhanced by the centrifugal instability in their study.…”
Section:  mentioning
confidence: 99%
“…The inspection of this study explained that eight-vortex chaotic flow enhanced the HC more than the two-vortex steady-state solution. Experimental observation of conjugate HT of turbulent flow is performed by Guo et al [36] in a 90 o curved square tube, where it was suggested the HT in a 90 o bent channel is 20% higher rather than in a straight channel. In the present work, Dolon et al [33] completed spectral-based computational modeling on flow and heat transition for a CRD of strong curvature (0.5) and large aspect ratio (Ar = 4.0) where various flow regimes are obtained and CHT is substantially enhanced by the centrifugal instability in their study.…”
Section:  mentioning
confidence: 99%
“…They concluded that the Nusselt number increased under the pulsation frequency where the structural resonance of the pipe occurred. In a separate study, Guo et al [18] induced a pulsating flow (Rem=60000, fp=30 Hz) by installing a rotating disk in a pipe, and evaluated the heat flux for both curved and straight pipes. Their findings suggest that the bend augments the heat transfer, a trend that persists even in the presence of pulsation.…”
Section: Introductionmentioning
confidence: 99%
“…Basiak et al [ 16 ] investigated two-phase flow, with an emphasis on velocity visualization and assessment. While Guo et al [ 17 ] performed thermal analysis, it was only for one frequency at a high flow rate.…”
Section: Introductionmentioning
confidence: 99%